Sociopreneurship sebagai Strategi Inovasi dalam Pengembangan Kuliner Tradisional Ingkung Djawa Waroeng Ndesso - Qoniatunnimah Qoniatunnimah; Difa Rose Meilia; Sawaldi Waskito Aji; Anik Widiastuti (Pusat Riset dan Inovasi Nasional, 2026)
The development of Indonesia’s traditional cuisine faces significant hurdles as shifting consumer preferences increasingly favor modern food options. This trend necessitates innovative approaches to ensure local culinary heritage remains competitive. This study examines the role of sociopreneurship as an innovation strategy at Ingkung Djawa Waroeng Ndesso. Utilizing a descriptive qualitative design, the research gathered insights from the business owner and employees selected via purposive sampling. Data collection involved interviews, observations, and documentation, with validity ensured through source triangulation. The analysis followed the Miles and Huberman model, encompassing data reduction, presentation, and conclusion drawing. Findings reveal that implementing sociopreneurship effectively integrates economic and social objectives by preserving authentic recipes, empowering local communities, and generating employment. Key innovations include diversifying product offerings while maintaining authenticity and leveraging social media for strategic marketing. These results demonstrate that social entrepreneurship serves as a powerful mechanism for enhancing business competitiveness while safeguarding cultural sustainability. The study implies that traditional culinary development can be successfully managed through a sociopreneurial framework, allowing for modern innovation without compromising core cultural values. Consequently, this model offers a sustainable pathway for traditional businesses to thrive amidst the challenges of contemporary market globalization.